Ruski emigranti, likovni umjetnici i njihov doprinos umjetnosti karikature - Medarić, Magdalena (Array, 2001)
The article dals with difference between two terms common among the Russian artists. They are "caricature" and "charge"Both of them can be applied not only to visual arts, but also to an intermedial sphere - of needed. However, the article is contered on the historical survey, that is on the works of Russian emigre graphic artists published on local periodicals, Croatian and Yugoslav, (1920-1940) that have influenced local cultural scene.